Double CD4/CD8-Positive, Nonpoikilodermic Mycosis Fungoides Expressing CD56 in a Young Man. (19th December 2022) - Santonja, Carlos; Sánchez-García, Francisco-Javier; Rodríguez-Rodríguez, Rosa-Nieves; Manso, Rebeca; Requena, Luis; Gil-Mateo, María del Pino; Rodríguez-Pinilla, Socorro-María
Abstract: We report a case of mycosis fungoides (MF) in an 18-year-old man whose neoplastic T cells expressed CD4, CD8, and CD56, with no evidence of TCR-delta or Epstein–Barr virus (EBER) expression. Clinically, neither hypopigmentation nor hyperpigmentation nor poikilodermatous skin lesions were present, and the lesions subsided with oral corticoids and retinoids and environmental solar ultraviolet exposure. Our case represents the oldest patient reported so far with nonpoikilodermatous, CD8/CD56 MF and adds to the phenotypic diversity of MF in the pediatric population. This distinct phenotype does not seem to be linked to a more aggressive course than the classic CD-4 positive one.